Political Economic Dilemma of Gulf Cooperation Council (GCC) Member Countries - Gilang Rizki Aji Putra; Nur Rohim Yunus; Atep Abdurofiq (BULETIN ADALAH, 2023)
This article examines the political and economic dilemma faced by member countries of the Gulf Cooperation Council (GCC). The GCC consists of six countries in the Gulf region that have abundant natural resources, especially oil and gas. These dilemmas include high dependence on revenues from the energy sector, challenges of economic diversification, imbalanced economic development among GCC members, as well as complex regional geopolitical influences. This paper also offers several policy recommendations to strengthen regional economic integration and reduce dependence on the energy sector, with the aim of maintaining economic stability and sustainability in the region.